2003
DOI: 10.1007/bf03033374
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural deficits following postnatal iron overload: II instrumental learning performance

Abstract: Three experiments reporting instrumental learning deficits following postnatal iron overload in rodents are described. In Experiment I, NMRI mice were given different doses of iron succinate (0.0, 3.7 or 37.0 mg Fe 2+ /kg b.w., p.o.) on different postnatal days (PD). In the PD 10-12 group, there were marked disruptions of radial arm maze learning performance in the 37.0 mg Fe 2+ /kg dose group, and to a lesser extent in the 3.7 mg Fe 2+ /kg dose group. In Experiment II, newborn NMRI mice were administered Fe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 84 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Effect of subchronic neuroleptic administration on the functional result of iron overload As demonstrated in several previous studies [75,76,78,[91][92][93][94][95] and confirmed again in the present study, postnatal administration of Fe 2+ (7.5 mg/kg, on Days 10-12) increased the level of iron in the adult mice (Fe-Veh group) to 168% of the Veh-Veh control mice; this concentration is roughly comparable, although at the lower range, to those presented in Fredriksson and Archer [77]. In the Fredriksson et al [92] Study, the analysis of the effects of the 7.5 mg Fe 2+ /kg, administered during postnatal days 10-12 to NMRI mice, upon iron content in the basal ganglia, indicated an increase of 148% in comparison with the associated vehicle control group values.…”
Section: Discussionmentioning
confidence: 80%
“…Effect of subchronic neuroleptic administration on the functional result of iron overload As demonstrated in several previous studies [75,76,78,[91][92][93][94][95] and confirmed again in the present study, postnatal administration of Fe 2+ (7.5 mg/kg, on Days 10-12) increased the level of iron in the adult mice (Fe-Veh group) to 168% of the Veh-Veh control mice; this concentration is roughly comparable, although at the lower range, to those presented in Fredriksson and Archer [77]. In the Fredriksson et al [92] Study, the analysis of the effects of the 7.5 mg Fe 2+ /kg, administered during postnatal days 10-12 to NMRI mice, upon iron content in the basal ganglia, indicated an increase of 148% in comparison with the associated vehicle control group values.…”
Section: Discussionmentioning
confidence: 80%